The Effectiveness of Cognitive Behavior Therapy Counseling to Reduce The Social Anxiety of Blind Students (Universitas Negeri Semarang, 2019)
This study aimed to examine the effectiveness of Cognitive Behavior Therapy counseling to reduce the social anxiety of blind students in Jepon State Special Schools or Sekolah Luar Biasa (SLB) Negeri Jepon. To achieve such objective, the study used single-subject design with the pattern of multiple baselines across individuals done in eleven sessions of observation, namely three baseline A1 sessions, five times intervention session, and three baseline A2 sessions. For more, the subjects of this study were two blind students indicated experiencing social anxiety. In this state, behavior target was reduced from social anxiety behavior. Meanwhile, the data of the observed subjects were collected thorough direct observation method with Goal Attainment Scale guides. Further, visual graph analyses were carried out to look for mean, the degree of level of performance, rapidity behavior change, the trend of performance, stability levels, and overlap data which were then followed by t score and z score calculations. The results showed that Cognitive Behavior Therapy counseling was able to reduce social anxiety. Therefore, the undertaken study asserts that Cognitive Behavior Therapy counseling is effective to reduce the social anxiety of the blind students in SLB Negeri Jepon.